Sistema de apoio à decisão: avaliação de cenários de gestão integrada de resíduos sólidos urbanos domiciliares - Massukado, Luciana Miyoko (Universidade Federal de São Carlos, 2004)
The amount of waste generated by human activities associated with the decrease of appropriate final disposal sites have been presented as one of the great challenges to be faced by local administrations as well as by waste generating communities. Nowadays, household solid waste management is analyzed according to Descartes and Newton models, which are characterized by the separation and analysis of a system through its parts, resulting in isolated and narrow sighted decisions. Aspects such as the lack of technical training and financial resources contribute to this ongoing scenario. Considering the exposed problem this work aims to develop a decision support system to support the managers in the evaluation household solid waste management scenarios. The method consisted in defining and delimiting the work field of decision support system, followed by the construction of a conceptual model based on the acquired knowledge. The model was then translated in action screens and decision workflows, which were programmed in Delphi 6.0. The Extreme Programming (XP) methodology was applied, meaning that programmer and cognitive agent act together in the code of the system. Finally, the validation of the SIMGERE software in São Carlos (São Paulo State) was made in two moments - first on program s usability, in other words, if the system is friendly and easy understanding by user for treating of a new environment for him and; second on the coherence of the results obtained by the simulation of the municipal household solid waste management. For São Carlos case study, the landfill lifetime projection, nearly 2 years, was coherent with the expected. However, the economical simulation needs to be revised in order to better reflect the current management model.
Keywords: Resíduos sólidos; Gestão de resíduos sólidos; Sistema de apoio à decisão; Cenários; SIMGERE; Household solid waste management; Decision support system; Scenario; SIMGERE; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO::RESIDUOS SOLIDOS, DOMESTICOS E INDUSTRIAIS